FUNGSI MUSIK KESENIAN HADRAH DI DESA SEKUDUK KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - rahman, Nur; Sanulita, Henny; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was motivated by the fact that Hadrah art is rarely heard among the public. The phenomenon is characterized by a lack of interest of teenagers to the Hadrah arts. The method used is descriptive method with a form of qualitative research. The approach used is an ethnographic approach. Source of data obtained through informants who know about Hadrah art in the Sekuduk village Sejangkung sub-district of Sambas district. Data collection techniques were observation, interview techniques, and technical documentation. Technique of validity the data was extension of the observation and triangulation sources techniques. The results of the research were: 1) the musical function of Hadrah art as the atmosphere carrier, as a means of communication, as a eans of education, as a means of survival and stability of culture, and as a means of entertainment. 2) the way of presenting Hadrah art such as percussion ensembles using seven kinds of musical instruments, which is 3 pieces of tambourines, drums, bongos, tambourines and maracas. The implementation of Hadrah arts besides performed at the Maulud Prophet, it was also commonly carried out at the marriage, circumcision, plain flour, halal bi halal, moved a new home, and salvation Umrah / Haj. Keywords:  Function, Forms of presentation, Hadrah arts